HOMOSSEXUALIDADE FEMININA: PERCEPÇÃO DA ENFERMAGEM SOBRE ASSISTÊNCIA EM SAÚDE - Duarte, Geneci Maria Londero (2017)
Brazil presented important advancements concerning Public Policies to qualify the health care to homosexuals in the last decade. Nursing care in the health services must be offered in its integrality and individuality, ensuring a welcoming care to this population, guaranteeing their rights and prerogatives. However, homophobic prejudice is still an obstacle to the health promotion in this context. The present study aimed to know the conception of Nursing professionals about the quality of the health care provided to homosexual women. The research had a qualitative approach and 20 nursing professionals participated. Two focus groups and four semi-structured interviews were developed for the data collection in an inner city in Rio Grande do Sul between June and July 2016. The material obtained during the collection was recorded in audio and later fully transcribed for the content analysis. The results obtained were thought the Bardin analysis method. From this analysis two manuscript. Manuscript one: Perception of the Nursing Care to Homosexual Women; Manuscript two: Nursing Treatment to the Homosexual Woman: The Focus Group Technique as a Training Strategy to the Nursing Staff. There is a need for continuing education by the extension of knowledge aiming at the improvement of the Nursing assistance provided to this population. The focus group technique is a valuable resource, it can be used in the Nursing field for research purposes, collection of the Nursing staff needs and the construction of training programs in the continuing education. Thereby, it is necessary and important to include this thematic in the Nursing professionals’ education in addition to trainings that allow an appropriated care to the singularities of homosexual women.